2014
DOI: 10.1371/journal.ppat.1004043
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Spatio-Temporal Dynamics of Imported DNA and ComE DNA Uptake Protein during Gonococcal Transformation

Abstract: Competence for transformation is widespread among bacterial species. In the case of Gram-negative systems, a key step to transformation is the import of DNA across the outer membrane. Although multiple factors are known to affect DNA transport, little is known about the dynamics of DNA import. Here, we characterized the spatio-temporal dynamics of DNA import into the periplasm of Neisseria gonorrhoeae. DNA was imported into the periplasm at random locations around the cell contour. Subsequently, it was recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
80
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 46 publications
9
80
0
Order By: Relevance
“…Moreover, previous reports have shown that ComE binds DNA and is essential for DNA uptake (22). In the absence of periplasmic DNA it is homogeneously distributed within the periplasm and relocates to the incoming DNA within minutes (23). The binding energy of ComE to DNA most likely provides the fuel for biasing diffusion of DNA through the secretin in the outer membrane.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Moreover, previous reports have shown that ComE binds DNA and is essential for DNA uptake (22). In the absence of periplasmic DNA it is homogeneously distributed within the periplasm and relocates to the incoming DNA within minutes (23). The binding energy of ComE to DNA most likely provides the fuel for biasing diffusion of DNA through the secretin in the outer membrane.…”
Section: Discussionmentioning
confidence: 97%
“…Within the periplasm, the DNAbinding protein ComE is essential for DNA uptake (22). In the absence of transforming DNA, ComE is distributed homogeneously within the periplasm and rapidly colocalizes with imported DNA (23,24). ComE governs the carrying capacity of the periplasm for DNA in a gene-dosage-dependent way (23).…”
mentioning
confidence: 99%
See 3 more Smart Citations